Akademiker Boris Petrovsky, Minister der Öffentlichen Gesundheit der Sowjetunion
soziale Fragen;Gesundheit;Gesundheitspolitik soziale Fragen;Gesundheit;Medizin soziale Fragen;Gesundheit;ärztlicher Beruf;Arzt/Ärztin soziale Fragen;Gesundheit;ärztlicher Beruf;arztähnlicher Beruf